Age-associated alterations in CD8α+ dendritic cells impair CD8 T-cell expansion in response to an intracellular bacterium - Li, Gang (Blackwell Publishing Ltd, 2012)
Age-associated decline in immunity to infection has been documented across multiple pathogens, yet the relative contributions of the aged priming environment and of lymphocyte-intrinsic defects remain unclear. To address the impact of the aging environment on T-cell priming, adult naïve OT-I TCR transgenic CD8 T cells, specific for the H-2K(b)-restricted immunodominant OVA(257-264) epitope, were transferred into adult or old recipient mice infected with the recombinant intracellular bacterium Listeria monocytogenes carrying the chicken ovalbumin protein (Lm-OVA). We consistently found that adult OT-I CD8 expansion was reduced in aged recipient mice, and this correlated with numeric, phenotypic, and functional defects selectively affecting CD8α+ dendritic cells (DC). Following Lm-OVA infection, aged mice failed to accumulate CD8α+ DC in the spleen, and these cells expressed much lower levels of critical costimulatory molecules in the first three days following infection. Further, aged CD8α+ DC showed impaired uptake of the bacteria at very early time points following infection. Treatment of aged mice with Flt3 ligand (Flt3L) improved the number of DC present in the spleen prior to Lm-OVA infection, and improved, but did not reconstitute, OT-I expansion to Lm-OVA infection. These results suggest that age-associated changes in antigen uptake, pathogen sensing, and/or antigen presentation contribute to impaired adaptive immune responses to microbial pathogens with aging.